Asuhan Keperawatan pada An. M dengan Post Operasi Debridement Indikasi Combustio Grade II di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Risma Zulianti; Ahmad Zakiudin; Esti Nur Janah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Combustio is an injury caused by fire chemicals, electricity which can cause skin and tissue damage (Antoro, 2023). The purpose of this writing is to find out and provide nursing care to An. M with post operative debridement indicating grade II combustio in the mawar room RSUD dr. Soeselo Kabupaten Tegal in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was foundthat the main complaint was pain. There were three diagnoses found, namely acute pain, impaired skin integrity and knowledge deficit. Interventions are prepared based on the theory of SDKI,SLKI, and SIKI as well as on the client’s condition and can be implemented.